Противороевое действие ТОС-3 на трутневом расплоде - Ишмуратова, Н.М.; Яковлева, М.П.; Тамбовцев, К.А.; Ишмуратов, Г.Ю. (Фактори експериментальної еволюції організмів, 2013)
Aims. Previously we suggested the way of antiswarm treatment bee-families bringing in nest-bowls of the pheromone preparation TOS-3 developed by us. The aim of this work is development of new method of antiswarm treatment using this preparation. Methods. A site of drone comb treated by the pheromone preparation TOS-3. Results. Considerable reduction of the area drone brood is noted when processing by the preparation TOS-3. Conclusions. Thus, sites of drone cells are biologically active zone of the bee nest which processing by a synthetic pheromone of a queen bee prevents emergence of swarm process at an early stage, and also reduces extent of defeat by varroatosis in the processed sites of comb.

Key words: pheromone, preparation TOS-3, antiswarm activity, drone brood.